2001
DOI: 10.1053/rapm.2001.27857
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine versus ketamine to prevent tourniquet pain during intravenous regional anesthesia with lidocaine

Abstract: The addition of clonidine 1 microg/kg or ketamine 0.1 mg/kg to lidocaine for IVRA delays the onset of unbearable tourniquet pain and decreases analgesic consumption for tourniquet pain relief, although ketamine has a more potent effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 27 publications
3
16
0
3
Order By: Relevance
“…The results of these tests were found to be without a significant effect [6]. Gorgias et al compared the efficacy of 1 mg/kg clonidine added to lidocaine for IVRA and found that clonidine delayed the onset of intense tourniquet pain and reduced the analgesic [14]. Reuben et al reported that clonidine could decrease the tourniquet pain as an adjuvant drug under IVRA [15].…”
Section: Discussionmentioning
confidence: 99%
“…The results of these tests were found to be without a significant effect [6]. Gorgias et al compared the efficacy of 1 mg/kg clonidine added to lidocaine for IVRA and found that clonidine delayed the onset of intense tourniquet pain and reduced the analgesic [14]. Reuben et al reported that clonidine could decrease the tourniquet pain as an adjuvant drug under IVRA [15].…”
Section: Discussionmentioning
confidence: 99%
“…254 Ketamine at a dose of 100 µg/kg has also been shown to improve tourniquet tolerance and reduce postoperative analgesic requirements in a manner that appears to be more potent than 1 µg/kg clonidine. 255 When compared with plain lidocaine, dexamethasone (8 mg) was recently shown to reduce postoperative analgesic requirements during the first 24 hours after surgery. 256 Given the multiple mechanisms that contribute to postoperative pain, the logical future study would involve a step-function assessment of serial additives and combinations of ketorolac, clonidine or dexmedetomidine, ketamine, and dexamethasone.…”
Section: Intravenous (Bier) Blockmentioning
confidence: 99%
“…124 Dexmedetomidine (0.5 mg/kg) has also shown benefi t. 131 Ketamine, at the dose of 100 µg/kg, has also been shown to improve tourniquet tolerance and reduce postoperative analgesic requirements, in a manner that appears to be more potent than clonidine at the 1-µg/kg dose. 132 When compared with plain lidocaine, dexamethasone (8 mg) was recently shown to reduce postoperative analgesic requirements during the fi rst 24 hours after surgery. 133 Given the multiple mechanisms contributing to postoperative pain, the logical future study would involve a step-function assessment of serial additives and combinations, with the additives to be considered including ketorolac, clonidine or dexmedetomidine, ketamine, and dexamethasone.…”
Section: (Bier) Blockmentioning
confidence: 99%